2018
DOI: 10.1111/pde.13728
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous CD4+ small‐ to medium‐sized pleomorphic T‐cell lymphoproliferative disorder in a pediatric patient successfully treated with low‐dose radiation

Abstract: Primary cutaneous CD4+ small‐ to medium‐sized pleomorphic T‐cell lymphoproliferative disorder (PCSM‐LPD) is a rare and low‐grade form of cutaneous T‐cell proliferation with the average age of diagnosis of 54 years. Because of its rarity, the etiology or exact clinicopathology of PCSM‐LPD remains unclear, with < 10 pediatric cases reported. A 13‐year‐old boy presented to our clinic with a raised tumor with PCSM‐LPD histology and was successfully treated with ultra‐low‐dose radiation therapy. While no standard o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A literature review of previously reported pediatric cases (defined as patients aged less than 18 years at time of initial reported presentation) of PCSM-TCLPD identified 13 additional cases (Table 1), not including our case above. [5][6][7][8][9][10][11][12][13] The mean age of patients was 10.6 years (range 0.5-16 years). One patient had multifocal lesions, 5 and the remaining 12 had solitary lesions (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review of previously reported pediatric cases (defined as patients aged less than 18 years at time of initial reported presentation) of PCSM-TCLPD identified 13 additional cases (Table 1), not including our case above. [5][6][7][8][9][10][11][12][13] The mean age of patients was 10.6 years (range 0.5-16 years). One patient had multifocal lesions, 5 and the remaining 12 had solitary lesions (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The most common treatment was local surgical excision, either as monotherapy or in combination with topical steroids (6/13); all excision-treated cases achieved a complete response. 5,[8][9][10] Other reported treatments have included intralesional corticosteroids (3/13) [11][12][13] and radiation therapy (2/13). 7,13 All but one of the cases reported in the literature to date with available outcomes data had complete response to therapy with a mean follow-up time of 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation